THU0167 Impact of Methotrexate Dose Reduction upon Initiation of Adalimumab on Clinical and Ultrasonographic Parameters in Patients with Moderate to Severe Rheumatoid Arthritis. (10th June 2014) - Kaeley, G.; Evangelisto, A.M.; Nishio, M.J.; Liu, S.; Kupper, H.
Abstract : Background: Methotrexate (MTX) is the recommended first-line disease-modifying antirheumatic drug (DMARD) for the treatment of moderately to severely active rheumatoid arthritis (RA).Whether patients (pts) with inadequate response to MTX initiating combination therapy with adalimumab (ADA) can reduce MTX dose remains unclear. Clinical and ultrasonographic (US) outcomes of MTX dose reduction upon initiating ADA were examined. Methods: MUSICA, a double-blind, parallel-arm, randomised, controlled trial, examined the impact of MTX dosage on disease and US outcomes in pts with moderately to severely active RA who have failed prior synthetic DMARDs. MUSICA enrolled 309 pts taking MTX ≥15 mg/week (wk) for ≥12 wks prior to enrollment. Pts received either blinded high- (20 mg/wk) or low-dosage (7.5 mg/wk) MTX; all pts received open-label 40 mg ADA every other wk for 24 wks. Non-inferiority was assessed using the 95% confidence interval (CI) of the difference between high and low dose wk-24 outcomes using a 15% non-inferiority margin; Disease activity score based on 28 joints (DAS28) was the primary endpoint. Ultrasound images acquired every 4 wks were independently read and scored blindly by 2 of 4 ultrasound-experienced rheumatologists. A bilateral 5-joint semi-quantitative scoring system incorporating OMERACT definitions 1 for pathology measured synovial hypertrophy and vascularity; bony erosions were scored as present or absent. Results: The study populations for both MTX dosages had similar baseline demographics (mean age 54.8, mean 5.3 years disease duration) and disease characteristics (mean DAS28 of 5.8). After 24 wks of ADA combination therapy, notable improvements in clinical indices were observed in both treatment groups, consistent with other trials including a low-dose MTX group. Differences in clinical, functional, and US outcomes between treatment groups were minimal. Although the wk-24 mean DAS28 difference (0.37) was within the non-inferiority margin (0.56), the primary endpoint was not met because the difference CI crossed the non-inferiority margin. Low-dosage MTX+ADA met non-inferiority for the proportion of pts achieving secondary endpoints, ACR70 and ΔHAQ-DI ≤-0.22. No statistically significant differences were detected for most clinical, functional, and ultrasound outcomes (Table). Excessive fatigue and/or malaise and abnormal hair loss were more prevalent in the low-dose MTX+ADA group. Conclusions: Addition of ADA to MTX inadequate responders led to clinically meaningful results consistent with prior studies. Week-24 mean DAS28, the primary endpoint, did not meet non-inferiority; however, the small differences in clinical, functional, and US outcomes suggest MTX dosage reduction might be considered when initiating adalimumab therapy in some MTX inadequate-responders. References: D'Agostino MA et al. 2009. J Rheumatol 36: 1829-32 Acknowledgements: AbbVie sponsored the study (NCT01185288 ), participated to its design, the collection, analysis, and interpretation of the data, and in the writing, reviewing, and approval of the final version. Medical writing support was provided by Douglas E. Dylla, PhD of AbbVie Inc. Disclosure of Interest: : G. Kaeley Consultant for: AbbVie, Inc., A. Evangelisto Grant/research support: AbbVie, Inc., Speakers bureau: AbbVie, Inc., M. Nishio Speakers bureau: AbbVie, Inc., S. Liu: None declared, H. Kupper: None declared DOI: 10.1136/annrheumdis-2014-eular.1133